PENGARUH PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MADRASAH TSANAWIYAH AL-IHSAN - Mustika, Helma; Hasanah, Musikatun (Jurnal Math-UMB.EDU, 2020)
This study began with many students having low concept comprehension skills. This can be seen from the learning process that there are still many students who are less active, and there are still many students who still get grades below the KKM. the purpose of this study was to determine the ability to understand students 'mathematical concepts using the Think Talk Write learning model better than students' ability to understand mathematical concepts using conventional learning models in class VIII MTs Al-Ihsan. The type of this research is experimental, the design is Quasi Experimental, with Randomized Subjects Posstest Only Control Group Design. The sampling technique in this study is cluster random sampling, where class VIII.3 was chosen as the experimental class and class VIII.5 as the control class. Data collection techniques through concept understanding tests, then data analysis techniques used are inferential statistical analysis using the "t" test (Independent Sample t Test). Based on the results of research testing the hypothesis of this study obtained t count = 2.061 t table = -1.999. This means that the ability to understand mathematical concepts of students using Think Talk Write learning models is better than the ability to understand mathematical concepts of students using conventional learning models in class VIII MTs Al-Ihsan